Integrating network pharmacology and experimental validation to clarify the anti-hyperuricemia mechanism of cortex phellodendri in mice - Lieqiang Xu; Juanjuan Cheng; Jieyi Lu; Guoshu Lin; Qiuxia Yu; Yucui Li; Jiannan Chen; Jianhui Xie; Ziren Su; Qi Zhou; Qi Zhou (Frontiers in Pharmacology, 2022)
Hyperuricemia (HUA), a common metabolic disease, is treated as the second-largest metabolic disease after diabetes in China. Cortex Phellodendri (CP) is one of the most frequently used herbal medicines for treating gout or HUA. However, the mechanism underlying the anti-HUA effect of CP is still unrevealed. Hence, this study aimed to explore the pharmacological mechanism of CP against HUA using network pharmacology coupled with in vivo experimental validation. Active compounds and potential targets of CP, as well as the potential targets related to HUA, were retrieved from multiple open-source databases. The drug-disease overlapping targets were obtained by Venn diagram analysis and used to construct the herb-component-target (HCT), protein-protein-interaction (PPI), and component-target-pathway (CTP) networks. The functional enrichment analysis was also performed for further study. Furthermore, a HUA mouse model was induced by a combination of intraperitoneal injection of potassium oxonate (PO, 300 mg/kg) and intragastric administration of hypoxanthine (HX, 300 mg/kg) daily for 10 days. Different dosages of CP (200, 400, and 800 mg/kg) were orally given to mice 1 h after modeling. The results showed that 12 bioactive compounds and 122 drug-disease overlapping targets were obtained by matching 415 CP-related targets and 679 HUA-related targets, and berberine was one of the most important compounds with the highest degree value. The core targets of CP for treating HUA were TP53, MAPK8, MAPK3, IL-6, c-Jun, AKT1, xanthine oxidase (XOD), and ATP-binding cassette subfamily G member 2 (ABCG2). The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment results showed that the anti-HUA effect of CP mainly involved the pathways of inflammation and apoptosis, such as PI3K/Akt, TNF, MAPK, TLR, AMPK, NF-κB, and NLRP3 signaling pathways. In vivo animal experiment further confirmed the hypouricemic effect of CP in a HUA mouse model, as evidenced by significantly restored kidney histological deteriorations, and considerably decreased levels of serum uric acid (sUA), creatinine (Cre), blood urea nitrogen (BUN), and hepatic UA. Furthermore, the hypouricemic action of CP in vivo might be attributed to its suppression of XOD activity in the liver, rather than ABCG2 in the kidney. Real-time qPCR (RT-qPCR) and Western blot analysis also confirmed the key roles of the hub genes in CP against HUA. In conclusion, CP exhibited therapeutic effect against HUA via multi-compounds, multi-targets, and multi-pathways. It possessed anti-HUA and nephroprotective effects via suppressing XOD activity, and reversed the progression of renal injury by exerting anti-inflammatory and anti-apoptotic effects.